A new tribe, novel and resurrected genera, and new species in Araceae - Wong, Sin Yeng (Faculty of Resource Science and Technology (FRST), 2010)
A new tribe, 4 new genera, two resurrected genera and 19 novel species were described betlveen 2008 - 2010 based on a combination of vegetative and reproductive morphology and molecular analyses.